PKC-δ, its C2 domain and breast cancer cell lines - Scott, Hannah Elizabeth (2012)
Protein kinase C δ (PKC-δ) is a novel member of the PKC family of serine-threonine kinases. PKC-δ structure is widely conserved within the PKC family and has a catalytic region and regulatory region. The regulatory region has two main sub domains C1 and C2. Although several studies have investigated the role of the C1 domain, little is known about the function of the C2 domain, however there is some evidence that it acts as a protein interaction domain.